PENGARUH MEDIA SCRAPBOOK TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPAS KELAS IV SDN 94 SINGKAWANG - Nanda, Deya; Marhayani, Dina Anika; Yanti, Lili (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine: (1) the difference in learning outcomes between the experimental class using scrapbook media and the control class using conventional learning in the Natural and Social Sciences (IPAS) subject for grade IV students at SDN 94 Singkawang, and (2) the extent of the influence of scrapbook media on students’ learning outcomes. The study employed a quantitative approach with a quasi-experimental method, using a Nonequivalent Posttest-Only Control Group Design. The sample consisted of 48 fourth-grade students divided into experimental and control groups. Data analysis involved prerequisite tests (normality and homogeneity) followed by a two-sample t-test and effect size analysis. The results revealed a significant difference in learning outcomes between the experimental and control groups, with a t-value of 7.5227 greater than the t-table value of 2.00856. Furthermore, the effect size analysis showed a value of 1.08, categorized as a high effect (ES > 0.8). These findings indicate that the use of scrapbook media has a significant and strong influence on improving students’ learning outcomes in the IPAS subject.